Development of Interactive Markerless Augmented Reality Media for the Human Respiratory System in Grade VIII Junior High School Science - Garcinia Mangostana Juarsyah; Abna Hidayati; Fitri Maiziani; Rosmaria (Indonesian Technology and Education Journal, 2026)
This study aimed to develop and evaluate an interactive Markerless Augmented Reality (AR) learning medium for the human respiratory system topic in Grade VIII Junior High School science, addressing the limitations of conventional instructional media in visualizing abstract internal physiological processes that cannot be directly observed by students. A Research and Development (R&D) approach was employed using the 4D development model (Define, Design, Develop, Disseminate), with the media developed using Unity, Vuforia Engine, Blender, and Figma and delivered as an Android application; data were collected through material and media validation questionnaires, a student practicality questionnaire, and pre-test/post-test instruments analysed using the Normalized Gain (N-Gain) formula. Material validation yielded 96.25% (Very Valid), media validation reached 98.67% (Very Valid) after two iterative revision rounds, practicality testing with 32 Grade VIII students produced 94.69% (Very Practical), and effectiveness testing yielded a mean N-Gain of 0.62, categorized as Moderate according to Hake's (1998) framework and classified as Effective enough based on the percentage criteria applied in this study, with post-test mean (85.00) surpassing the minimum mastery criterion of 80. The developed media demonstrates strong potential as a promising model for technology-based science instruction at the junior high school level; however, the findings are subject to limitations as the study was conducted within a single school, covered a single content topic, was restricted to Android platform compatibility, and was evaluated within a single instructional session, which may limit the generalisability of the results. This study contributes an empirically validated Markerless AR application specifically developed for the human respiratory system, an abstract internal physiological topic at the Grade VIII level that remains comparatively underserved in existing AR-based science education research, with the integrated evaluation of validity, practicality, and effectiveness within a single 4D development cycle offering a methodologically complete quality-assurance framework for future AR media developers.